ANALISIS SISTEM PENGENDALIAN INTERNAL TERHADAP PERSEDIAAN PADA PT. XYZ PONTIANAK - B51112096, Irwan Setiawan (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
Inventory is goods purchased and then stored for sale in the normal operation of the company so that the company always gives a great attention in inventory. Due to the highly strategic position in the company as a source of income. Inventories are very vulnerable to damage, incorrect entry, inattentive record demand, the goods issued not as ordered, and all the other possibilities that can lead to inventory records differ from the actual inventory in the warehouse. Considering the importance of maintaining the existing inventory at the company required an effective internal control system. The purpose of this research is to determine the effectiveness and feasibility of the internal control system over inventory, determine the factors that influence its effectiveness rate. The study case in PT. XYS Pontianak is using four analytical techniques to decide its effectiveness rate, which is organizational structure analysis, flowchart evaluation, Internal Control Questionnaire (ICQ) and Compliance Test. From all the analytical method, we can conclude that the internal control system over inventory that is in use by PT. XYZ Pontianak is quite effective. The internal control is influenced by some factor, there is employees mutation rate that quite high, the persistence of dual labor, and lack of direct control by management. Keywords: Internal Control System, Inventory